Nitrogen retention and partitioning at the initiation of lipid accumulation in nitrogen‐deficient algae. Issue 2 (25th February 2014) - Adams, Curtis; Bugbee, Bruce; Buschmann, A.
<x xml:space="preserve">Abstract</x> Nitrogen (N) deficiency promotes lipid accumulation in many oleaginous algae, but we have a poor understanding of the associations between the initiation of lipid accumulation and algal N retention and partitioning. Here, we report on total cell N, five bulk pools of N in the cell (protein, free amino acids, DNA, RNA, chl), and lipids from N saturation to growth cessation in three species. While the maximum level of N uptake differed among species, the ratio of minimum retained N to N retained at the initiation of lipid accumulation was consistent among species at 0.5 ± 0.04. This suggests that the cellular initiation of lipid accumulation was associated with a common magnitude of N deficiency among species. Concerning the partitioning of N, the concentration of RNA and the protein to RNA ratio were most similar among species at the initiation of lipid accumulation with averages of 3.2 ± 0.26 g · L−1 (8.2% variation) and 16 ± 1.5 (9.2% variation), respectively. All other pools and physiologically relevant ratios were considerably more variable. The species commonalities in RNA and protein show a similar reduction in general cellular function due to N deficiency before cellular initiation of lipid accumulation. These results provide insight into the physiological drivers for lipid accumulation in N‐deficient algae and data for modeling these associations.